Superior efficacy of insulin degludec/liraglutide versus insulin glargine U100 as add‐on to sodium‐glucose co‐transporter‐2 inhibitor therapy: A randomized clinical trial in people with uncontrolled type 2 diabetes. Issue 6 (4th April 2019) - Philis‐Tsimikas, Athena; Billings, Liana K.; Busch, Robert; Portillo, Cristobal Morales; Sahay, Rakesh; Halladin, Natalie; Eggert, Sarah; Begtrup, Kamilla; Harris, Stewart
Abstract : Aim: To investigate the efficacy and safety of insulin degludec/liraglutide (IDegLira) versus insulin glargine 100 units/mL (IGlar U100) as add‐on to sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor therapy. Materials and methods: In this 26‐week, phase IIIb, open‐label, parallel‐group, treat‐to‐target trial, conducted at 74 sites in 11 countries, insulin‐naïve people aged ≥18 years with glycated haemoglobin (HbA1c) 53–97 mmol/mol (7.0–11.0%), body mass index 20–40 kg/m 2 and inadequately controlled type 2 diabetes (T2D) on SGLT2 inhibitor ± oral antidiabetic drugs were randomized 1:1 to once‐daily IDegLira or IGlar U100, both as add‐on to existing therapy. The primary endpoint was change in HbA1c from baseline to week 26. Results: A total of 210 participants were randomized to each treatment arm. Mean HbA1c reductions were 21 mmol/mol (1.9%‐points) with IDegLira and 18 mmol/mol (1.7%‐points) with IGlar U100; confirming non‐inferiority ( P  < 0.0001) and superiority of IDegLira (difference in HbA1c change –3.90 mmol/mol; 95% confidence interval [CI] –5.45; –2.35 (−0.36%‐points; 95% CI –0.50, –0.21)). Superiority for IDegLira over IGlar U100 was also confirmed for: body weight (difference −1.92 kg; 95% CI –2.64, –1.19); severe or blood‐glucose‐confirmed symptomatic hypoglycaemia (rate ratio 0.42; 95% CI 0.23, 0.75); total daily insulin dose (difference −15.37 U; 95% CI –19.60, −11.13). The overall treatment‐emergent adverse event rate was higher with IDegLira as a result of higher increased lipase and nausea rates. Conclusions: The favourable safety and efficacy profile of IDegLira in people with uncontrolled T2D on SGLT2 inhibitors, and lower weight gain and hypoglycaemia risk versus IGlar U100, suggest that clinicians should consider IDegLira initiation in this population.